2017
DOI: 10.1002/mnfr.201700496
|View full text |Cite
|
Sign up to set email alerts
|

Ser71 of αS1‐Casein is Phosphorylated in Breast Milk—Evidence from Targeted Mass Analysis

Abstract: Phospho-occupancy rates varied greatly and could not be confidently correlated to other parameters within the cohort of 20 donors. The new phosphosite S71 is located in the neighborhood of the serine-rich region and may contribute to the cluster of high charge density at normal milk pH, likely exerting an influence on protein tertiary structure and thus function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Therefore, S 33 and S 41 could be more easily accessible for kinases. In accordance, it was found before that S 33 and S 41 of human αS1-casein [31] and stretch 85-102 of bovine αS1-casein were phosphorylated in significant amounts. Opposite to this, only low levels of phosphorylation were described for the hydrophobic stretch 83-102 of human αS1-casein, especially for S 89 [14,31].…”
Section: Hydrophobicity Analysis Of Human αS1-casein and Comparison W...supporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, S 33 and S 41 could be more easily accessible for kinases. In accordance, it was found before that S 33 and S 41 of human αS1-casein [31] and stretch 85-102 of bovine αS1-casein were phosphorylated in significant amounts. Opposite to this, only low levels of phosphorylation were described for the hydrophobic stretch 83-102 of human αS1-casein, especially for S 89 [14,31].…”
Section: Hydrophobicity Analysis Of Human αS1-casein and Comparison W...supporting
confidence: 90%
“…In accordance, it was found before that S 33 and S 41 of human αS1-casein [31] and stretch 85-102 of bovine αS1-casein were phosphorylated in significant amounts. Opposite to this, only low levels of phosphorylation were described for the hydrophobic stretch 83-102 of human αS1-casein, especially for S 89 [14,31]. The low level of phosphorylation in stretch 83-102 of human αS1-casein indicated that it was less accessible for kinases, although it was found to be more hydrophobic than in bovine αS1-casein.…”
Section: Hydrophobicity Analysis Of Human αS1-casein and Comparison W...supporting
confidence: 90%
See 2 more Smart Citations
“…α-S1-casein is best known as a highly phosphorylated protein harboring close to a dozen phosphorylation sites. Among these phosphorylation sites, Ser71, which has recently been reported to be phosphorylated in breast milk, 26 happens to be in the sequon of the N-glycosylation we found (NES) and, thus, on the peptide stretch we monitored. This opens the question of whether a potential positive or negative crosstalk between Nglycosylation and phosphorylation may occur.…”
Section: Identification Of Novel N-glycosylation Sitesmentioning
confidence: 99%